2010
DOI: 10.1007/s00540-010-1034-y
|View full text |Cite
|
Sign up to set email alerts
|

Colloid solutions: a clinical update

Abstract: Albumin, dextran, gelatin, and hydroxyethyl starch (HES) solutions are colloids that efficiently expand the circulating blood volume. The administration of colloids restores the intravascular volume with minimal risk of tissue edema in comparison with crystalloid solutions alone. However, colloids are always given for surgical and critically ill patients. The type of the colloid, volumes applied, aggressiveness of fluid resuscitation, and the volume status at the initial phase of administration determine their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 127 publications
(131 reference statements)
0
40
0
3
Order By: Relevance
“…Because the pharmacokinetics of the chaser would likely affect the efficiency of labeling, we administered either a small molecular tetrazine fluorophore (MW 1.3 kDa) or polymer modified tetrazines (PMT) using two differently sized dextrans: 10 kDa (PMT10) and 40 kDa (PMT40). Dextrans were chosen as polymer scaffold due to their low cost, high stability, and numerous previous in vivo applications (18)(19)(20). These amine modified scaffolds were modified on average with approximately one fluorochrome and either two (PMT10) or eleven (PMT40) tetrazines as measured using absorption spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the pharmacokinetics of the chaser would likely affect the efficiency of labeling, we administered either a small molecular tetrazine fluorophore (MW 1.3 kDa) or polymer modified tetrazines (PMT) using two differently sized dextrans: 10 kDa (PMT10) and 40 kDa (PMT40). Dextrans were chosen as polymer scaffold due to their low cost, high stability, and numerous previous in vivo applications (18)(19)(20). These amine modified scaffolds were modified on average with approximately one fluorochrome and either two (PMT10) or eleven (PMT40) tetrazines as measured using absorption spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Based on modeling of reaction kinetics and PK clearance rates, we designed and tested specific polymer-tetrazine adducts bearing "imaging" reporters (near infrared fluorochromes and 18 F) to visualize reactions in live mice both at the cellular and whole animal level. The current generation of polymer-tetrazine conjugates included dextran derivatives (PMT10 and PMT40) because dextrans have a long history of in vivo use and the PK are well understood (18)(19)(20). Based on the kinetics of the TCO component, we would envision that the PMT could be based on a number of different polymers for further optimization (e.g., PEGs, PL, PLGA, nanoparticles, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HSA infusions have multiple effects, such as volume expansion, increase of the colloid osmotic pressure, and hemodilution. Although the use of HSA therapy in different clinical situations and its influence in morbidity and mortality remains controversial, advantages of HSA therapy in the management of ascites and the use of HSA in volume expansion have been reported (De Gaudio, 1995;Peters, 1996;Wilkes and Navickis, 2001;Mendez et al, 2005a;Myburgh and Finfer, 2009;Niemi et al, 2010;Bunn et al, 2011).…”
Section: Human Serum Albumin Therapy In Clinical Practicementioning
confidence: 95%
“…Colloids including HSA are widely used as plasma substitutes for short-term replacement of fluid volume in critically ill patients efficiently expanding the circulating blood volume (Peters, 1996;Myburgh and Finfer, 2009;Niemi et al, 2010;Bunn et al, 2011). Up to about 25% of administered HSA is for the treatment of acute hypovolemia following surgical blood loss, trauma, and hemorrhage.…”
Section: Parenteral Uses Of Human Serum Albuminmentioning
confidence: 98%
“…18 Osmotic nephrosis-like lesions, a decrease in tubular flow during glomerular filtration of colloids, and an accumulation of small molecules in the tubuli have been proposed to explain the deleterious effects of highmolecular-weight starches on renal function. 19 However, a recent systematic review reported that there is no indication in the actual literature that the use of tetrastarches induces adverse renal effect in surgical patients. 17 In addition, a …”
Section: Discussionmentioning
confidence: 99%